2022
DOI: 10.1364/boe.447595
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear distortion correction for posterior eye segment optical coherence tomography with application to tree shrews

Abstract: We propose an empirical distortion correction approach for optical coherence tomography (OCT) devices that use a fan-scanning pattern to image the posterior eye segment. Two types of reference markers were used to empirically estimate the distortion correction approach in tree shrew eyes: retinal curvature from MRI images and implanted glass beads of known diameter. Performance was tested by correcting distorted images of the optic nerve head. In small animal eyes, our purposed method effectively reduced nonli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A study by Quihong L. et al (2001) [ 33 ] documented a similar phenomenon where OCT retinal thickness measures were greater than those measured by histology; however, when the data were normalized, there were no significant differences between the two methods. One explanation for the smaller values measured via histological sections is tissue shrinkage and dehydration during the enucleation and fixation processes; additionally, it has been demonstrated that OCT can introduce measurement bias [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Quihong L. et al (2001) [ 33 ] documented a similar phenomenon where OCT retinal thickness measures were greater than those measured by histology; however, when the data were normalized, there were no significant differences between the two methods. One explanation for the smaller values measured via histological sections is tissue shrinkage and dehydration during the enucleation and fixation processes; additionally, it has been demonstrated that OCT can introduce measurement bias [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…While larger animals, such as dogs, swine, and primates, have greater anatomical homology to humans, their use is limited by the cost of cohorts and ethical considerations. Tree shrews may be considered as an alternative glaucoma animal model given the presence of the laminar cribrosa in the eyes of these small animals ( 27 ). The ability to access refined measurements of glaucoma pathology in a longitudinal and non-invasive manner could improve the usability of these models moving forward ( 91 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…Panda et al and Braeu et al employed these AI-driven approaches to identify novel morphological biomarkers for glaucoma in humans ( 20 , 26 ). These technologies were then successfully ‘reverse-translated’ in the tree shrew model ( 27 ) to better understand non-linear optical distortions present in OCT images. This knowledge could ultimately improve our glaucoma predictions in patients.…”
Section: Areas Of Research Opportunities For Reverse Translation Of A...mentioning
confidence: 99%
“…As a result, OCT image analysis is inaccurate because of the spatial and optical distortions. In order to increase the accuracy of the curvature of surfaces and thickness between intermediate layers, distortion correction for OCT images is highly desired [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%